2017
DOI: 10.1097/pcc.0000000000001171
|View full text |Cite
|
Sign up to set email alerts
|

Lung Rest During Extracorporeal Membrane Oxygenation for Neonatal Respiratory Failure—Practice Variations and Outcomes

Abstract: Objective Describe practice variations in ventilator strategies used for lung rest during extracorporeal membrane oxygenation (ECMO) for respiratory failure in neonates, and assess the potential impact of various lung rest strategies on the duration of ECMO and the duration of mechanical ventilation after decannulation. Data Source Retrospective cohort analysis from the extracorporeal life support organization (ELSO) registry database during the years 2008–2013. Study selection All ECMO runs for infants ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…We noted higher use of nonconventional modes during ECMO than reported previously, although most adult studies of mechanical ventilation on ECMO have used conventional mechanical ventilation exclusively, with a few recent studies reporting small number of subjects on airway pressure release ventilation. [6][7][8][9][10][11]17,27 Neonates on ECMO predominantly receive conventional mechanical ventilation (88%). 11 There was variability in some ventilator settings, including F IO 2 and mean airway pressure ( P aw ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We noted higher use of nonconventional modes during ECMO than reported previously, although most adult studies of mechanical ventilation on ECMO have used conventional mechanical ventilation exclusively, with a few recent studies reporting small number of subjects on airway pressure release ventilation. [6][7][8][9][10][11]17,27 Neonates on ECMO predominantly receive conventional mechanical ventilation (88%). 11 There was variability in some ventilator settings, including F IO 2 and mean airway pressure ( P aw ).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11]17,27 Neonates on ECMO predominantly receive conventional mechanical ventilation (88%). 11 There was variability in some ventilator settings, including F IO 2 and mean airway pressure ( P aw ). The median values of F IO 2 and P aw in our study were lower than reported in adult studies, but the variability was similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent cohort study, it was shown that the use of HFV compared with conventional mechanical ventilation (MV) for lung rest during ECMO support is associated with longer duration of ECMO and MV (24). We used conventional MV modes for lung rest strategies during ECMO run for all our patients, regardless of their illness type and severity.…”
Section: Discussionmentioning
confidence: 99%